FLEXIBLE WORKING ARRANGEMENTS, WORK ENGAGEMENT, WORK-LIFE BALANCE, JOB SATISFACTION, AND EMPLOYEE PERFORMANCE - Mochammad Abduh Hamzah; Bachtiar Usman (Multifinance, 2026)
The increasing adoption of Flexible Working Arrangements (FWA) in public organizations has transformed human resource management practices, particularly in enhancing employee productivity while maintaining service quality. However, empirical evidence regarding the mechanisms through which FWA influences employee performance in the public sector remains limited. This study aims to examine the effects of Flexible Working Arrangements, Work Engagement, and Work-Life Balance on Work Performance, with Job Satisfaction serving as a mediating variable among employees of the West Java Provincial Transportation Agency. A quantitative research design with a cross-sectional survey approach was employed. Data were collected from 242 employees selected through stratified random sampling from a population of 613 employees. The research data were analyzed using Structural Equation Modeling (SEM) with AMOS to evaluate both the measurement and structural models. The findings indicate that the proposed SEM model achieved acceptable goodness-of-fit criteria, confirming its suitability for explaining the relationships among the studied variables. The results further reveal that Flexible Working Arrangements, Work Engagement, and Work-Life Balance each have positive and significant effects on Job Satisfaction. In addition, these variables directly and positively influence Work Performance. Job Satisfaction also has a significant positive effect on Work Performance and acts as a significant mediating variable in the relationships between Flexible Working Arrangements, Work Engagement, Work-Life Balance, and Work Performance. These findings suggest that improving employee performance requires an integrated human resource management strategy that combines flexible work policies, employee engagement initiatives, and work-life balance programs while simultaneously enhancing job satisfaction. This study contributes to the human resource management literature by providing empirical evidence from Indonesia's public sector and offers practical recommendations for policymakers in developing adaptive, employee-centered work policies to support sustainable bureaucratic transformation and improved public service performance.